2018
DOI: 10.3390/math6020020
|View full text |Cite
|
Sign up to set email alerts
|

Finite Automata Capturing Winning Sequences for All Possible Variants of the PQ Penny Flip Game

Abstract: Abstract:The meticulous study of finite automata has produced many important and useful results. Automata are simple yet efficient finite state machines that can be utilized in a plethora of situations. It comes, therefore, as no surprise that they have been used in classic game theory in order to model players and their actions. Game theory has recently been influenced by ideas from the field of quantum computation. As a result, quantum versions of classic games have already been introduced and studied. The P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 36 publications
4
18
0
Order By: Relevance
“…Another related problem, namely that of quantum gambling based on the Nash-equilibrium was examined in [10]. The association of every finite variant of the PQ penny flip game with finite automata, so that strategies are words accepted by the corresponding automaton, was established in [11]. In that work, the underlying assumption was that Q will always use the Hadamard operator.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Another related problem, namely that of quantum gambling based on the Nash-equilibrium was examined in [10]. The association of every finite variant of the PQ penny flip game with finite automata, so that strategies are words accepted by the corresponding automaton, was established in [11]. In that work, the underlying assumption was that Q will always use the Hadamard operator.…”
Section: Related Workmentioning
confidence: 99%
“…This was accomplished in [9] where the authors exploited entanglement in a clever way, so that whether the system ends up in a maximally entangled or separable state determines the outcome. In [11], it was shown that all possible finite extensions of the PQG can be expressed in terms of simple finite automata, provided that the allowable moves of Picard are either I or F and Q always uses the Hadamard transform H. The focus of the present investigation is enlarging the operational space of the game. Therefore, when considering extensions of the original PQG, not only the assumptions ( 24) and (41), i.e., M P = {I, F} and M Q = U(2) are valid, but, additionally, it is supposed that:…”
Section: Extending the Gamementioning
confidence: 99%
See 1 more Smart Citation
“…Automata in general have already been shown to be related to games and strategies in various works [31,32,38,39]. Andronikos et al established a sophisticated connection between finite automata and the PQ Penny game, constructing automata for various interesting variations of the game [39]. The proposed semiautomaton is capable of capturing the game's finite variations, introducing the notion of the winning and the complete automaton for either player.…”
Section: Related Workmentioning
confidence: 99%
“…Automata in general have already been shown to be related to games and strategies in various works [26,27,33,34]. Andronikos et al established a sophisticated connection between finite automata and the PQ Penny game, constructing automata for various interesting variations of the game [34]. The proposed semiautomaton is capable of capturing the game's finite variations, introducing the notion of the winning and the complete automaton for either player.…”
Section: Related Workmentioning
confidence: 99%